STUDY ON THE NEEDS OF COMPETENCIES AND ABILITIES FOR THE GRADUATES’ ADAPTATION TO THE REQUIREMENTS OF THE LABOUR MARKET IN THE CONTEXT OF EUROPE 2020 STRATEGY - ALINA-TEODORA CIUHUREANU; HORTENSIA GORSKI; NICOLAE BALTEŞ (Annals of the University of Petrosani: Economics)
The workforce competence is a core value for the development of a competitive, sustainable and innovative economy, in accordance with the objectives of Europe 2020. In times of budgetary constraints and unprecedented global competitive pressures, the European Union’s policies on employment and competencies that contribute to the shaping of the transition to a green, intelligent and innovative economy has to be a priority. Romania’s European Union accession is a major challenge for our country and implicitly for the Centre Region in terms of adapting the Romanian economic and social environment to the European one. Under this new context, the changes to ensure competitiveness will cause major changes in the field of employment and the workforce professional training. The development of the continuous vocational training system that would meet the requirements of the labour market and of a knowledge-based economy requires relevant information on the evolution of jobs and professions, the evolution tendencies of the labour market, the needs for competencies and qualifications of companies, the level of correlation between the demand and offer of workforce and the identification of gaps, the programmes’ offer of professional training suppliers and its suitability to the needs of applicants. These are some of the reasons that have contributed to the accomplishment of the study on the needs of competencies and abilities for the graduates’ adaptation to the requirements of the labour market in the context of Europe 2020 strategy.